Nasal epithelial barrier dysfunction increases sensitization and mast cell degranulation in the absence of allergic inflammation. Issue 5 (18th December 2019) - Kortekaas Krohn, Inge; Seys, Sven F.; Lund, Gitte; Jonckheere, Anne‐Charlotte; Dierckx de Casterlé, Isabelle; Ceuppens, Jan L.; Steelant, Brecht; Hellings, Peter W.
Abstract: Background: Increased epithelial permeability has been reported in allergic rhinitis, with histamine and type‐2 inflammation being responsible for tight junction dysfunction. The impact of an epithelial barrier defect on allergic sensitization and mast cell (MC) degranulation remains speculative. Methods: Transepithelial passage of allergens was evaluated on primary human nasal epithelial cell cultures. Active sensitization was attempted by repeated intranasal ovalbumin (OVA) applications in Naïve mice. In a passive sensitization model, mice were injected with IgE to Dermatophagoides pteronyssinus (r Der p )2 and then exposed intranasally to the allergen. Chitosan was used to disrupt nasal epithelial integrity in vitro and in vivo . Results: Chitosan strongly reduced transepithelial electrical resistance and facilitated transepithelial allergen passage in cultured primary nasal epithelial cells. In vivo, intranasal chitosan affected occludin expression and facilitated allergen passage. After epithelial barrier disruption, intranasal OVA application induced higher OVA‐specific IgG1 and total IgE in serum, and increased eosinophilia and interleukin‐5 in bronchoalveolar lavage (BAL) compared to sham‐OVA mice. Chitosan exposure, prior to r Der p 2 allergen challenge in passively sensitized mice, resulted in increased β‐hexosaminidase levels in serum and BAL compared to sham‐r Der p 2 mice. Intranasal treatment with the synthetic glucocorticoid fluticasone propionate prevented chitosan‐induced barrier dysfunction, allergic sensitization, and MC degranulation. Conclusion: Epithelial barrier dysfunction facilitates transepithelial allergen passage, allergic sensitization, and allergen‐induced MC degranulation even in the absence of inflammatory environment. These results emphasize the crucial role of an intact epithelial barrier in prevention of allergy. Abstract : Maintenance of the epithelial barrier function is essential to prevent allergic sensitization and mast cell degranulation. Fluticasone propionate is effective to preserve an intact epithelial barrier. Epithelial barrier dysfunction increases allergen passage and facilitates allergic sensitization. Re‐exposure of allergens to a defective barrier can activate mast cell degranulation even in the absence of an ongoing inflammation.